Design of a hydraulically driven compressive elastocaloric cooling system. (3rd July 2016) - Qian, Suxin; Geng, Yunlong; Wang, Yi; Muehlbauer, Jan; Ling, Jiazhen; Hwang, Yunho; Radermacher, Reinhard; Takeuchi, Ichiro
Abstract : This article presents the design of elastocaloric cooling system driven by hydraulic actuators. Ni-Ti tubes under axial compressive loading mode are used in the system to provide cooling and heating. Those Ni-Ti tubes are enclosed in four identical beds, which are driven by two one-way hydraulic cylinders. Operated under the single-stage reverse Brayton cycle, the system achieves heat transfer and heat recovery by using a sophisticated heat transfer fluid network controlled by solenoid valves. Two novel designs to improve the system's performance based on the lessons learned from the previous studies are applied to this prototype. Preliminary test results of the material's latent heat at a specific fluid flow rate and temperature difference agree well with the results reported in the literature. System coefficient of performance of 11.0 and temperature lift of 24.6 K are estimated based on a dynamic model developed in the previous study.